Formulation And In- Vitro Evaluation Of Gastro Retentive Floating Matrix Tablets Of Famotidine Formulation And In-Vitro Evaluation Of Gastro Retentive Floating Matrix Tablets Of Famotidine - JADHAV MAYUR N.; S. SHANMUGAM; K. SUNDARAMOORTHY; T. AYYAPPAN; T. VETRICHELVAN (International Journal of Pharma and Bio Sciences, 2010)
The purpose of this investigation was to prepare a gastro retentive drug delivery system of Famotidine. Floating tablets of Famotidine were prepared by employing polymers like Guar gum and Xanthan gum by effervescent technique. The tablets were prepared by direct compression method. The polymers were used individually as well as in combination to formulate floating tablets. Sodium bicarbonate was incorporated as a gas generating agent. The floating tablets were evaluated for physicochemical parameters such as hardness, weight variation, percent friability, floating properties (floating lag time, total floating time and matrix integrity), swelling studies, drug content, stability study and In vitro drug release. The drug polymer interaction was studied by DSC thermal analysis. The physicochemical parameters of formulated tablets were found to be within normal range. The floating lag time of all the formulations was within the prescribed limit (<10 minutes). All the formulations showed good matrix integrity and retarded the release of drug for ten hours except the formulations F1, F2 and F3. The release pattern of Famotidine was fitted to different models based on coefficient of correlation(r). The swelling studies of all the formulations showed that formulations containing combination of Guar gum and Xanthan gum has higher swelling indices than individual Guar gum and Xanthan gum. Optimized formulation (F7) of Famotidine floating tablet was found to be stable for storage at 40°C/75% relative humidity for 3 months.